THE EFFECT OF INTEGRATING SCRABBLE INTO NUMBERED HEADS TOGETHER ON STUDENTSâ€™ VOCABULARY ACHIEVEMENT AT GRADE SEVEN OF SMP NEGERI 12 KONAWE SELATAN - Marliyanti, Marliyanti; Tanduklangi, Amri; Alberth, Alberth (Universitas Halu Oleo, 2019)
This study aimed at finding out whether there is a significant effect of integrating scrabble into numbered heads together at grade seven of SMP Negeri 12 Konawe Selatan or not. The research was conducted to answer the following question â€œIs there any significant effect of integrating scrabble into numbered heads together on studentsâ€™ vocabulary achievement at grade seven of SMP Negeri 12 Konawe Selatan?â€. The hypothesis of this research is â€œThere is a significant effect of integrating scrabble into numbered heads together on studentsâ€™ vocabulary achievement at grade seven of SMP Negeri 12 Konawe Selatanâ€. This research used quasi experimental design with population was all grade seven students at SMPÂ Â NegeriÂ Â 12Â Â KonaweÂ Â Selatan in academic year 2018/2019. The samples of this research were class VIIE as the experimental class and VIIB as control class. The experimental class consist of 28 students and control class consist of 26 students. The research instrument was 40 questions of vocabulary test. Collecting the data, the researcher gave pre-test, taught integrating scrabble into numbered heads together, and giving post-test. The result show that studentsâ€™ mean score in experimental class are 55.21 at pre-test and 75.13 at post-test, while studentsâ€™ mean score in control class are 55.61 in pre-test and 64.93 in post-test. Based on the calculation of T-test, it shows that the score of tcount Â = 5.636 is higher than ttableÂ = 2.007 and the pvalue= 0.000 is lower thanÂ Â = 0.05. Therefore, the null hypothesis is rejected and H is accepted. This can be conclude that there is a significant effect of integrating scrabble into numbered heads together on studentsâ€™ vocabulary achievement at grade seven students of SMP Negeri 12 Konawe Selatan.Â Keywords:Â Scrabble, numberedÂ heads together, vocabularyÂ achievement